Evolusi dan Tipologi Data OpenStreetMap di Daerah Istimewa Yogyakarta Tahun 2015–2025 - Totok Wahyu Wibowo; Purwanto Purwanto; Ahmad Haikal (Progresif: Jurnal Ilmiah Komputer, 2026)
OpenStreetMap (OSM) data in the Special Region of Yogyakarta grew rapidly during 2015–2025, but the distribution of this growth across object types and administrative areas remains insufficiently understood. This study aims to examine the evolution of road networks, buildings, and points of interest (POIs), develop a cross-object growth typology, and evaluate the relative structure of OSM data. Historical data were obtained through the ohsome API and aggregated at the subdistrict/kemantren level. The analysis covered absolute change, growth rates, percentile-rank scores, and the Road–Building Ratio (RBR), Building–POI Ratio (BPR), and Amenity–Tourism Ratio (ATR). Buildings showed the strongest growth, roads developed through coverage expansion and segment refinement, while POIs grew more moderately despite sharp increases in shop and tourism features. The typology identified multi-object growth, road-dominant, building-dominant, POI-dominant, and low-growth patterns. Structural ratios indicated the growing dominance of buildings and an imbalance between physical objects and functional information.Keywords: Special Region of Yogyakarta; spatio-temporal evolution; OpenStreetMap; POI; growth typologyAbstrakData OpenStreetMap (OSM) di Daerah Istimewa Yogyakarta berkembang pesat selama 2015–2025, tetapi pemerataan pertumbuhan antarobjek dan antarwilayah belum dipahami secara sistematis. Penelitian ini bertujuan menganalisis evolusi jaringan jalan, bangunan, dan points of interest (POI), menyusun tipologi pertumbuhan lintas objek, serta mengevaluasi struktur relatif data OSM. Data historis diperoleh melalui ohsome API dan diagregasikan pada tingkat kecamatan/kemantren. Analisis mencakup perubahan absolut, laju pertumbuhan, skor percentile rank, serta Road–Building Ratio (RBR), Building–POI Ratio (BPR), dan Amenity–Tourism Ratio (ATR). Hasil menunjukkan bahwa bangunan tumbuh paling kuat, jaringan jalan berkembang melalui perluasan cakupan dan pendetailan segmen, sedangkan POI tumbuh lebih moderat meskipun kategori shop dan tourism meningkat tajam. Tipologi menghasilkan pola multi-object growth, road-dominant, building-dominant, POI-dominant, dan low-growth. Rasio struktural menunjukkan penguatan dominasi bangunan dan ketidakseimbangan antara objek fisik dan informasi fungsi ruang.Kata kunci: Daerah Istimewa Yogyakarta; evolusi spasio-temporal; OpenStreetMap; POI; tipologi pertumbuhan